Selective Wnt/β-Catenin Pathway Activation Concomitant With Sustained Overexpression of miR-21 is Responsible for Aristolochic Acid-Induced AKI-to-CKD Transition - Kuang, Qing; Wu, Sheng; Xue, Ning; Wang, Xiaoyan; Ding, Xiaoqianq; Fang, Yi (Frontiers in Pharmacology, 2021)
Acute kidney injury (AKI) is increasingly recognized as a cumulative risk factor for chronic kidney disease (CKD) progression. However, the underlying mechanisms remain unclear. Using an aristolochic acid (AA)-induced mouse model of AKI-to-CKD transition, we found that the development of tubulointerstitial fibrosis following AKI was accompanied with a strong activation of miR-21 and canonical Wnt signaling, whereas inhibition of miR-21 or selective silencing of Wnt ligands partially attenuated AKI-to-CKD transition. To explore the interaction between miR-21 and Wnt/β-catenin signaling, we examined the effects of genetic absence or pharmacologic inhibition of miR-21 on Wnt/β-catenin pathway expression. In miR-21–/– mice and in wild-type mice treated with anti-miR-21 oligos, Wnt1 and Wnt4 canonical signaling in the renal tissue was significantly reduced, with partial reversal of renal interstitial fibrosis. Although the renal abundance of miR-21 remained unchanged after inhibition or activation of Wnt/β-catenin signaling, early intervention with ICG-001, a β-catenin inhibitor, significantly attenuated renal interstitial fibrosis. Moreover, early (within 24 h), but not late β-catenin inhibition after AA administration attenuated AA-induced apoptosis and inflammation. In conclusion, inhibition of miR-21 or β-catenin signaling may be an effective approach to prevent AKI-to-CKD progression.